2012
DOI: 10.1371/journal.ppat.1002854
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Virulence Strategy for Pseudomonas aeruginosa Mediated by an Autotransporter with Arginine-Specific Aminopeptidase Activity

Abstract: The opportunistic human pathogen, Pseudomonas aeruginosa, is a major cause of infections in chronic wounds, burns and the lungs of cystic fibrosis patients. The P. aeruginosa genome encodes at least three proteins exhibiting the characteristic three domain structure of autotransporters, but much remains to be understood about the functions of these three proteins and their role in pathogenicity. Autotransporters are the largest family of secreted proteins in Gram-negative bacteria, and those characterised are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 122 publications
(118 reference statements)
0
52
0
Order By: Relevance
“…The bacterial strains and plasmids used in this study are listed in Table 1. P. aeruginosa strains were cultured at 37°C in double yeast tryptone (dYT) medium or minimal medium P (MMP) (10). For growth assays, MMP was modified by omitting NH 4 Cl (MMP-N) so that various peptides could be used as sole nitrogen sources.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are listed in Table 1. P. aeruginosa strains were cultured at 37°C in double yeast tryptone (dYT) medium or minimal medium P (MMP) (10). For growth assays, MMP was modified by omitting NH 4 Cl (MMP-N) so that various peptides could be used as sole nitrogen sources.…”
Section: Methodsmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a well‐known opportunistic pathogen that causes a variety of diseases in predisposed individuals . The virulence of P. aeruginosa is largely related to its ability to secrete into the environment an immense battery of virulence factors . In the present study, we investigated the Ser/Thr/Tyr phosphorylated extracellular proteins that remain unexplored up to now.…”
Section: Extracellular Proteins Identified In Two Experimentsmentioning
confidence: 99%
“…Several P. aeruginosa proteases have been isolated and shown to be involved in pathogenesis. Of the proteases analysed, alkaline protease (AprA) (Kharazmi, 1991), elastase (LasA and LasB) (Preston et al, 1997;Suter, 1994), protease IV (PrpL) (Engel et al, 1998;O'Callaghan et al, 1996), small protease (PasP) (Marquart et al, 2005;Tang et al, 2009), immunomodulating metalloprotease (ImpA) (Bardoel et al, 2012), aminopeptidase (Luckett et al, 2012), large extracellular protease (LepA) (Kida et al, 2008(Kida et al, , 2011 and extracellular serine protease (EprS) (Kida et al, 2013) have been characterized extensively. We previously reported that EprS, an autotransporter protease of P. aeruginosa, induces host inflammatory responses through protease-activated receptors (PARs) (Kida et al, 2013).…”
Section: Introductionmentioning
confidence: 99%